The potential of snail seromucous and chitosan as bioimunomodulator for tuberculosis therapy - Sutanto, Yusup Subagio; Sutanto, Magdalena; Agnes Sri Harti,; Nony Puspawati, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Tuberculosis (TB) as a global emergency is a chronic disease caused by Mycobacterium tuberculosis (Mtb). Mtb plays an important role in inducing or suppressing the production of Interferon Gamma (IFNG) and IL-4 in the regulation of TB homeostasis and pathogenesis. The bioactive compounds of the snail seromucous (Achatina fulica Ferussac) and chitosan function as biological response modifiers. The study aimed to determine the potential effectiveness of snail seromucous and chitosan as bio-immunomodulator for TB therapy. The research method was based on the results of laboratory experiments with the physic-chemical, biochemical, microbiological examination, snail seromucous protein profile, lymphocyte proliferation, measurement of IFNG, and IL-4 levels. The results of the physic-chemical examination of the snail seromucous showed a specific gravity of 1.010; pH 8, glucose 16 mg/dL; cholesterol 9 mg/dL; protein 2.8 mg/dL and heavy metals (Pb, Cu, Hg, Al) negative. The results of microbiological tests showed that a 100% concentration of snail seromucous was antimicrobial against Staphylococcus aureus, Candida albicans, and Pseudomonas aeruginosa. The protein profile of snail seromucous shows that there are 3 protein subunits, namely the range 55 - 72 kDa and 1 specific protein sub-unit 43 kDa as a bioactive compound achasin sulfate. Addition of chitosan dose of 65 μg/mL; snail seromucous dose of 65 μg/mL and a mixture of chitosan (65 μg/mL): snail seromucous (65 μg/mL) ratio 1: 1, can increase lymphocyte proliferation; optimum levels of IFN-γ and IL-4. Snail seromucous and chitosan are effective immunomodulators and potential candidates for TB therapy.